2019
DOI: 10.1108/mrr-07-2018-0266
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of frontline employee service innovative behavior

Abstract: Purpose The purpose of this study is to examine the influence of workplace happiness and work engagement on employee service innovative behavior from the perspective of positive psychology. The study also examines if work engagement mediates the relationship between workplace happiness and employee service innovative behavior. Finally, it investigates how co-worker socializing and the service climate of the organization moderate the relationship between work engagement and employee service innovative behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…110,111 That is to say, when the overall organizational environment will helpful to augment employees' innovative behavior, employees of that organization will normally attempt to follow these embedded norms and will act innovatively 112,113 by watching their coworkers and leaders' innovative behavior. 114,115 Once a particular environment is sustained in the firm, it becomes a guiding principle for an innovative work process that not only guides but also leads to more innovative behavior. 115,116 In summary, the leaders who recognize an innovative firm's environment are found to be more empowered, and they exploit their intellectual assets to succeed in a dynamic and challenging business environment, and thus exhibit innovative behavior.…”
Section: A Firm's Innovative Environment and Innovative Work Behaviormentioning
confidence: 99%
“…110,111 That is to say, when the overall organizational environment will helpful to augment employees' innovative behavior, employees of that organization will normally attempt to follow these embedded norms and will act innovatively 112,113 by watching their coworkers and leaders' innovative behavior. 114,115 Once a particular environment is sustained in the firm, it becomes a guiding principle for an innovative work process that not only guides but also leads to more innovative behavior. 115,116 In summary, the leaders who recognize an innovative firm's environment are found to be more empowered, and they exploit their intellectual assets to succeed in a dynamic and challenging business environment, and thus exhibit innovative behavior.…”
Section: A Firm's Innovative Environment and Innovative Work Behaviormentioning
confidence: 99%
“…Perceived attainment value (AV) is another factor that encourages employees to create high-quality work since they perceive future success if they fulfil their responsibilities effectively [13,14]. Moreover, according to the broaden-and-build theory, positive thinking (PT) can stimulate feelings through creative thought that then develops into behavioural repertoire to build specialised skills [15,16]. For both academics and researchers, the question arises whether factors of AV and PT are possible moderators of EE and IWB.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests management strategies for inspiring nurse innovative behaviour. Although earlier research confirmed the relationship between workplace fun and employee innovative behaviour (Abdullah et al., 2016; Al‐Hawari et al., 2019), in the cultural context of Chinese hospitals, the correlation between the above variables had not been confirmed. The function of affective commitment was unclear.…”
Section: Implication For Nursing Managementmentioning
confidence: 90%
“…Our results showed that workplace fun had a positive effect on Chinese nurse innovative behaviour ( r = .663, p < .01). Although there are almost no reports of similar studies in the field of nursing management, in other organisational environments, investigators have confirmed the relationship between workplace fun and employee innovative behaviour (Al‐Hawari et al., 2019; Fluegge‐Woolf, 2014). Our study results were consistent with previous studies in other countries.…”
Section: Discussionmentioning
confidence: 99%